Optimalisasi DMA IAIN untuk Menurunkan Kehilangan Air pada di Perumda Air Minum Tirta Giri Nata Kota Cirebon - Puspa, Puspa; Masduqi, Ali; Hastuti, Dian Suci (Universitas Tanjungpura, 2025)
District Meter Area (DMA) of IAIN has not compliance the National Non Revenue Water (NRW) target of 25% from January-December 2023. The NRW of DMA IAIN in 2023 is 44.38%. This research aims to analyse the existing conditions, identify causes of NRW, and arrange recommendations for the optimize DMA to reduce water loss. The analysis is analysing the water consumption pattern, water balance, Infrastructure Leakage Index (ILI) and Strength Weakness Oportunity Threats (SWOT) method. This DMA has fulfilled ideal condition except the division of subDMAs, the implementation of hydraulic modelling, and the implementation of IoT. There is an indication of leakage in the pipeline based on the pressure-discharge graph. The water loss is 44.26%. The ILI is 0 or good category (A1). The ATR performance indicator is 501 L/connection/day or very bad category (D). The DMA optimisation strategies to reduce and control water loss are planning alternative financial support, forming subDMA, applying Epanet for hydraulic modelling, installing loggers and SCADA as implementation of IoT, revitalising pipes and customer meters that has 10 years of technical age, finding active leaks such as executing step test, arranging water loss reduction and control SOP, ensuring the assets safety, and updating GIS data.